(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
Coconut water is a natural product reported to contain antioxidant compounds with beneficial health effects. This study aimed to evaluate the antidiabetic effect of mature coconut water on some biochemical parameters of liver and kidney functions, and histological architecture of the pancreas in alloxan-induced diabetic rats. Twenty-four (24) Wistar rats were randomly divided into four groups, (n=6). Group I (negative control) rats were fed with rat chow and drinking water ad libitum and did not receive alloxan. Group II (positive control) received a single intraperitoneal dose of 150mg/kg body weight of alloxan to induce type 1 diabetes mellitus. Groups III and IV received a single intraperitoneal dose of 150mg/kg body weight of alloxan and were treated with 1ml/kg of mature coconut water for 3 weeks and 2mg/kg of glibenclamide for 3 weeks respectively by oral administration. On day 21, blood samples were collected for liver and kidney function tests. Liver function tests for Group II showed elevated aspartate transaminase (AST), alkaline phosphatase (ALP), albumin, total protein, total bilirubin, and low alanine aminotransferase (ALT) (p<0.05). When compared with Group II, Group III showed elevated liver function parameters except ALT that was reduced (p<0.05). Group IV showed elevated AST, total bilirubin, and reduced ALT, ALP, albumin, and total protein (p<0.05). Kidney function tests showed that rats in Group II had significantly high creatinine, urea, bicarbonate, potassium, and sodium (p<0.05). Group III had lowered creatinine, potassium levels, but with elevated urea, bicarbonate, and sodium levels (p<0.05). Group IV had lowered creatinine, urea, bicarbonate, potassium levels, but with elevated sodium levels (p<0.05). This study indicates that mature coconut water can be included in the treatment regimen for diabetes mellitus due to its hepatorenal protective functions.